Electrode Dynamics - Fisher,A C (Oxford University Prese, 1996)
Electron transfer is of fundamental importance to the study of chemical reactivity. Investigation of electrode kinetics provides a unique method with which to explore the nature of electron transfer phenomena and construct models of its behaviour. Unlike conventional methods for studying chemical reactivity, electrochemical techniques provide an additional and powerful new tool with which to manipulate the rate of electron transfer reaction - the electrode potential. This text seeks to introduce students to the kinetics of electron transfer reactions and explore the potential applications of electrochemical methodology. The mathematical content has been purposely minimized for clarity throughout, whilst retaining the important results necessary for physical insight.